Inside Cover: Rational Design of an Apoptosis‐Inducing Photoreactive DNA Intercalator (Angew. Chem. Int. Ed. 24/2013). Issue 24 (28th May 2013) - Ueberschaar, Nico; Dahse, Hans‐Martin; Bretschneider, Tom; Hertweck, Christian
<x xml:space="preserve">Abstract</x> Vinylchartreusin, a chartreusin analogue that intercalates in double‐stranded DNA, was prepared by mutasynthesis to design a photoactivatable antitumoral agent that is able to form [2+2] photoadducts. In their Communication on page 6185 ff., C. Hertweck and co‐workers report substantially higher antiproliferative activities of this compound compared with the natural product upon irradiation with visible light. Colorectal cancer cells (see background) show signs of apoptosis after treatment with vinylchartreusin and blue light.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>